Emission characteristics of PCDD/Fs in stack gas from municipal solid waste incineration plants in Northern China. (June 2018) - Zhu, Feng; Li, Xiaofei; Lu, Jia-Wei; Hai, Jing; Zhang, Jieru; Xie, Bing; Hong, Chengyang
Abstract: Emission characteristics including congener's profile, gas emissions and toxic equivalent concentration (TEQ) indicators of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) in 57 stack gas samples from 6 municipal solid waste incinerators (MSWIs) in Northern China were investigated by gas chromatography-high resolution mass spectrometry (HRGC-HRMS). Additionally, PCDD/Fs formation mechanisms from the MSWIs were briefly discussed. Results revealed that the concentrations and equivalent concentrations of PCDD/Fs emissions in stack gas from 6 MSWIs were in the range of 0.11–2.53 ng Nm −3 and 0.007–0.059 ng TEQ Nm −3, respectively. The emission factors of PCDD/Fs from 6 MSWIs varied from 0.027 to 0.225 μg I-TEQ tonne −1, with a mean value of 0.17 μg I-TEQ tonne −1 waste, which was estimated to an annual emission of 234.96 mg I-TEQ of PCDD/Fs from 6 MSWIs to the atmosphere. O8CDD, O8CDF and 1, 2, 3, 4, 6, 7, 8-H7CDD were the indicatory compounds of PCDD/Fs to apportion the sources of PCDD/Fs in environmental medium especially in ambient environment of MSWIs. 1, 2, 3, 7, 8, 9-H6CDF and 1, 2, 3, 4, 7, 8-H6CDF can be used as TEQ indicators for monitoring PCDD/Fs emission. Based on the positive matrix factorization (PMF) model, eight factors were extracted by the PMF analysis. Formation of low-chlorinated PCDDs (1, 2, 3, 7, 8-P5CDD, 1, 2, 3, 4, 7, 8-H6CDD, 1, 2, 3, 6, 7, 8-H6CDD and 1, 2, 3, 7, 8, 9-H6CDD) possessed strong correlation, and the chlorophenols maybe the important precursors of low-chlorinated PCDDs, which were generated within the low chlorinated content. Penta- and hexa-PCDFs formation in stack gas from MSWI may block catalytic sites for PCDFs formation from carbon. Meanwhile, possible formation mechanisms of high-chlorinated PCDDs (hepta- and octa-PCDDs) and high-chlorinated PCDFs (hepta- and octa-PCDFs) were respectively dependent. Highlights: Emission factors of PCDD/Fs in stack gas from MSWIs were evaluated. The indicatory compounds of PCDD/Fs in stack gas were pointed out. 1, 2, 3, 7, 8, 9-H6CDF and 1, 2, 3, 4, 7, 8-H6CDF can be used as TEQ indicators. PCDD/Fs formation mechanisms were discussed through the PMF model.